Study of the quality index of groundwater (GWQI) and its use for irrigation purposes using the techniques of the geographic information system (GIS) of the plain Nekor-Ghiss (Morocco) - Elkhalki, S.; Hamed, R.; Jodeh, S.; Ghalit, M.; Elbarghmi, R.; Azzaoui, K.; Hanbali, G.; Ben Zhir, K.; Ait Taleb, B.; Zarrouk, A.; Lamhamdi, A. (Frontiers in Environmental Science, 2023)
Groundwater is an essential water supply for drinking water, agriculture and industry worldwide. In arid and semi-arid regions, groundwater has seriously deteriorated in recent decades due to environmental changes, anthropogenic activities and marine intrusion. A total of 79 groundwater samples from the Nekor-Ghiss plain were sampled for major chemical ion analysis. These analyzes showed that the water samples were highly mineralized (>1500 mg/L), with hardness (83.5% of the samples were very hard) and high concentrations of chemical elements, such as Cl-, Mg2+, Na+ and SO42-. To assess the quality of water in the study area for irrigation and consumption purposes, we used the quality index (GWQI) as well as a multi-criteria analysis based on “GIS” by assigning a weight to the different water quality parameters. Also, Piper and Durov diagram was investigated. The results of the study were focused on the water quality parameters of the collected groundwater samples, such as the sodium adsorption rate (SAR), the percentage of soluble sodium (Na%), the Residual Sodium Carbonate (RSC) and Permeability Index (PI) Majority of water samples in the study area are suitable to be used for irrigation. Magnesium Risk (MH) and Kelley's Ratio (KR). The suitability of groundwater samples for irrigation purposes is 51.9 % unsuitable samples to 59.49% good. Groundwater monitoring in terms of quality and quantity is essential for sustainable groundwater management. The results also shows that 92% of all samples are falling in the domain of Ca – Mg – HCO3 which frequently recharges water in limestone and dolomite aquifers and about 8% of the measured samples showed the water type of Ca-Na-Mg-HCO3